2007
DOI: 10.5194/aab-50-59-2007
|View full text |Cite
|
Sign up to set email alerts
|

Beef versus dairy cattle: a comparison of feed conversion, carcass composition, and meat quality

Abstract: Abstract. The objective of this study was to investigate the phenotypical differences in feed conversion, carcass composition, and meat quality of two cattle breeds representing either the accretion type (Charolais) or the secretion type (Holstein). Eighteen Charolais bulls and 18 German Holstein bulls were raised and fattened under identical conditions on a high energy level with concentrates and hay. The animals were slaughtered at the age of 18 months. Charolais bulls had a body weight (BW) of 750.6 kg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 25 publications
7
71
4
1
Order By: Relevance
“…This suggests that more than one locus is responsible for these fatrelated effects. The greater degree of fatness associated with the Holstein allele at these QTL is consistent with the findings of Pfuhl et al (2007), who showed that Charolais bulls have a decreased percentage of subcutaneous fat and decreased weights of internal fat deposits (e.g., gut, omental, kidney, and scrotum fat) than Holstein bulls.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This suggests that more than one locus is responsible for these fatrelated effects. The greater degree of fatness associated with the Holstein allele at these QTL is consistent with the findings of Pfuhl et al (2007), who showed that Charolais bulls have a decreased percentage of subcutaneous fat and decreased weights of internal fat deposits (e.g., gut, omental, kidney, and scrotum fat) than Holstein bulls.…”
Section: Discussionsupporting
confidence: 78%
“…The first of these positions is close to 2 other highly significant QTL detected on this chromosome for total saleable meat and rib lean proportion. For the QTL identified on this chromosome, the Charolais allele is associated with increased lean and saleable meat proportions and decreased bone proportion compared with the Holstein allele, which agrees with general comparisons between these 2 cattle breeds (Pfuhl et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Meat colour is one of the main parameters influencing consumer buying decisions and is affected by a number of different factors (reviewed by Mancini and Hunt, 2005). The lighter meat produced by the CH bulls in our study confirms the results of earlier breed comparisons (Chambaz et al, 2003;Pfuhl et al, 2007). The difference may be explained by different haem iron content in the muscle (Chambaz et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Biological differences among beef and dairy breeds in feed efficiency and utilization have been demonstrated by various researchers, usually from the perspective of beef production. Pfuhl et al (2007) found that Charolais bulls were more efficient in protein accretion than Holsteins, which directed more energy to producing fat. Robelin and Geay (1984) also reported leaner carcasses in the Charolais (and Limousin), relative to the Holstein, although other beef breeds had fatter carcasses.…”
Section: Resultsmentioning
confidence: 99%